Integration of a calcium looping process (CaL) to molten carbonate fuel cells (MCFCs), as carbon concentration system: First findings. (May 2018) - Della Pietra, M.; Santarelli, M.; Stendardo, S.; McPhail, S.; Perez-Trujillo, Juan Pedro; Elizalde-Blancas, Francisco
Highlights: Integration of CaL process with MCFC technology. Optimum working point of CaL + MCFC coupled together. Preliminary investigation of a new BOP Cal process pre-combustion CCS technology. Abstract: The utilisation of coal as fuel for the production of energy will grow parallel with the increase of the cost of oil in the next years. This paper aims to investigate the integration between two clean coal technologies: Calcium Looping (CaL) process and Molten Carbonate Fuel Cell (MCFC) in order to produce a high CO2 concentrated stream. The main goal of this work is to find out the optimum working point of a system using CaL and MCFC technologies, coupled together, to produce decarbonised energy from coal as a primary energy source. The integrated system of CaL with MCFC presented in this paper, is fed with a raw syngas coming from coal gasification [1]. The raw syngas is decarbonised using calcium oxide as solid sorbent in the first reactor of CaL (carbonator), subsequently the clean syngas flowing out of the carbonator is used as anodic fuel for an MCFC. The thermal regeneration of solid sorbents occurs burning methane with air producing a CO2 reach gas, that feeds the cathodic compartment of MCFC. This configuration allows to concentrate the CO2 from cathode side to anode side of the MCFC, using internal electrochemical reactions of the cell, producing electric power at the same time. This work has been structured to tackle the coupling of CaL with MCFC using a combined numerical and experimental approach. Thus the investigation of the possible integration has been carried out starting with a lumped model simulating the whole calcium looping process. The model was used to investigate the behaviour of the CaL system when varying the amount of solid sorbent used in the process. Data coming from the model in terms of gas composition flowing out from CaL reactors were subsequently validated experimentally simulating different operating conditions in a MCFC single cell (81 cm2). Performance of the MCFC was monitored with polarisation curves and power density curves, aiming to integrate experimentally the electric behaviour of the whole system, in order to have a first validation of the two systems working together.